Sanativo Wound Healing Product Does Not Accelerate Reepithelialization in a Mouse Cutaneous Wound Healing Model. Issue 2 (February 2017) - Marshall, Clement D.; Hu, Michael S.; Leavitt, Tripp; Barnes, Leandra A.; Cheung, Alexander T. M.; Malhotra, Samir; Lorenz, H. Peter; Delp, Scott L.; Quake, Stephen R.; Longaker, Michael T.
Abstract : Background: Sanativo is an over-the-counter Brazilian product derived from Amazon rainforest plant extract that is purported to improve the healing of skin wounds. Two experimental studies have shown accelerated closure of nonsplinted excisional wounds in rat models. However, these models allow for significant contraction of the wound and do not approximate healing in the tight skin of humans. Methods: Full-thickness excisional wounds were created on the dorsal skin of mice and were splinted with silicone rings, a model that forces the wound to heal by granulation and reepithelialization. Sanativo or a control solution was applied either daily or every other day to the wounds. Photographs were taken every other day, and the degree of reepithelialization of the wounds was determined. Results: With both daily and every-other-day applications, Sanativo delayed reepithelialization of the wounds. Average time to complete healing was faster with control solution versus Sanativo in the daily application group (9.4 versus 15.2 days; p < 0.0001) and the every-other-day application group (11 versus 13 days; p = 0.017). The size of visible scar at the last time point of the study was not significantly different between the groups, and no differences were found on histologic examination. Conclusions: Sanativo wound healing compound delayed wound reepithelialization in a mouse splinted excisional wound model that approximates human wound healing. The size of visible scar after complete healing was not improved with the application of Sanativo. These results should cast doubt on claims that this product can improve wound healing in humans.